The Toronto Concussion Study: a prospective investigation of characteristics in a cohort of adults from the general population seeking care following acute concussion, 2016–2020 - Comper, Paul; Foster, Evan; Chandra, Tharshini; Langer, Laura; Wiseman-Hakes, Catherine; Mochizuki, George; Ruttan, Lesley; Lawrence, David W.; Inness, Elizabeth L.; Gladstone, Jonathan; Saverino, Cristina; Tam, Alan; et al. (Frontiers in Neurology, 2023)
Purpose: There is limited research regarding the characteristics of those who seek care following acute concussion from the general population. Methods: To address this gap, a large cohort of 473 adults diagnosed with acute concussion (females=287; males=186) were followed using objective measures prospectively over 16 weeks beginning at a mean of 5.1 days post-injury. Results: Falls were the most common mechanism of injury (MOI) (n=137, 29.0%), followed by recreational sports-related (n=119, 25.2%). Males were more likely to be injured playing recreational sports or in a violence-related incident; females were more likely to be injured by falling. Post-traumatic amnesia (PTA) was reported by 80 participants (16.9 %) and loss of consciousness (LOC) was reported by 110 (23.3%). 54 participants (11.4%) reported both PTA and LOC. Males had significantly higher rates of PTA and LOC after their injury compared to their female counterparts. Higher initial symptom burden was associated with longer duration of recovery for both males and females. Female participants had more symptoms and higher severity symptoms at presentation compared to males. Females were identified to have a longer recovery duration, with a mean survival time of 6.50 weeks compared to 5.45 weeks in males (p<0.0001). A relatively high proportion of female and male participants in this study reported premorbid diagnoses of depression and anxiety compared to general population characteristics. Conclusion: Although premorbid diagnoses of depression and/or anxiety were associated with higher symptom burden at initial visit, duration of symptoms was not directly associated with pre-injury history of psychological/psychiatric disturbance. This cohort of adults seeking care for their acute concussion, from the general population, attained clinical and functional recovery over a period of 4 to 12 weeks.